Theoretical and methodological principles of application of event analysis in the activity of the patronage service of state administration - Kryvoshein, V. V. (Aspekty publichnoho upravlinni͡a, 2018)
The theoretical and methodological principles of application of the method of event analysis in the activity of the patronage service of the state administration body are considered. It is shown that using the method of event analysis it becomes possible to streamline the flow of socio-political events in such a way that through a series of phenomena to identify objective tendencies and on this basis to develop an objective assessment, to formulate and substantiate the forecast of the development of events. The typical scheme of the event analysis is given. It is disclosed that the method of event analysis involves a consistent description of the chain: the situation – events – the environment – the participants (their resources, interests, interconnections) – limitation of activities – goals and objectives (success / failure criteria) – alternative solutions – scenarios and forecasts – action strategy. The stages of the event analysis are singled out and procedures are described on each of them. In particular, the following stages of the event analysis are defined: compiling a data bank or join-ing an existing one; separation of the information array into separate units of observation and data sorting; calculation of results of filling matrix classifier; analytical comparison of the obtained values; verification of the results. Detailed procedures of the stage of creation of a data bank are described: the phases of the process of creating data about events are selected (choice of information support; development of coding system; choice of coding method; database creation); the structure of the information archive is determined (special abstracts, special indexes, specialized fund for formalized analysis of events, problems and documents); describes the main criteria for evaluating, selecting, refining and formalizing information (subject of the event, purpose, plan, idea of the subject of the event, action, image, form, means of action of the subject of the event, object, subject of the event, time (date) event, event location, result, product, event finale, event reason, event outcome, other special circumstances and event conditions). The advantages and disadvantages of the event analysis in the activity of the patronage service of the public administration body are revealed.